PERORAL ENDOSCOPIC MYOTOMY IN ESOPHAGEAL ACHALASIA: INTRAOPERATIVE COMPLICATIONS AND METHODS OF THEIR CORRECTION - M. P. Korolyov; L. E. Fedotov; A. L. Ogloblin; Sh. D. Mamedov; A. V. Klimov; L. A. Gabdrakhmanova (Вестник хирургии имени И.И. Грекова, 2016)
The authors analyzed complications in peroral endoscopic myotomy in case of esophageal achalasia in 27 patients. There were noted hypercapnia, carboxyperitoneum, hemorrhage, perforation of mucous coat of esophagus. These complications were suppressed during endoscopic manipulations.